Adaptation and evaluation of the measurement properties of the Brazilian version of the Self-efficacy for Appropriate Medication Adherence Scale - Rafaela Batista dos Santos Pedrosa; Roberta Cunha Matheus Rodrigues (Universidade de São Paulo, 2016)
Objectives: to undertake the cultural adaptation of, and to evaluate the measurement properties of, the Brazilian version of the Self-efficacy for Appropriate Medication Adherence Scale in coronary heart disease (CHD) patients, with outpatient monitoring at a teaching hospital. Method: the process of cultural adaptation was undertaken in accordance with the international literature. The data were obtained from 147 CHD patients, through the application of the sociodemographic/clinical characterization instrument, and of the Brazilian versions of the Morisky Self-Reported Measure of Medication Adherence Scale, the General Perceived Self-Efficacy Scale, and the Self-efficacy for Appropriate Medication Adherence Scale. Results: the Brazilian version of the Self-efficacy for Appropriate Medication Adherence Scale presented evidence of semantic-idiomatic, conceptual and cultural equivalencies, with high acceptability and practicality. The floor effect was evidenced for the total score and for the domains of the scale studied. The findings evidenced the measure's reliability. The domains of the Brazilian version of the Self-efficacy for Appropriate Medication Adherence Scale presented significant inverse correlations of moderate to strong magnitude between the scores of the Morisky scale, indicating convergent validity, although correlations with the measure of general self-efficacy were not evidenced. The validity of known groups was supported, as the scale discriminated between "adherents" and "non-adherents" to the medications, as well as to "sufficient dose" and "insufficient dose". Conclusion: the Brazilian version of the Self-efficacy for Appropriate Medication Adherence Scale presented evidence of reliability and validity in coronary heart disease outpatients.